Matoš and Whitman: a Comparison of Two Poems - Mitrovich, Ksenija; Swanson, Martha (Poznańskie Studia Slawistyczne, 2014)
This essay compares Utjeha kose, translated as The Solace of Hair, by Antun Gustav Matoš and Death’s Valley by Walt Whitman. We analyze similarities in theme, metaphor and poetic style. We also offer a close analysis of verse, together with meter, together with syntax and phonology of the two poems. Matoš and Whitman approach similar themes from different perspectives. However, we find coincidental similarities in both techniques and stylistic devices and the underlying messages of the pieces. We also draw upon our personal vision of the pieces as well as, in the case of Death’s Valley in particular, outside sources, to form our opinions. It is necessary to say that we had no access to any materials on Matoš, and, therefore, all our statements on The Solace of Hair are our personal conclusions and have no intext or works cited documentation.